Konstruksi tema-rema dalam bahasa Indonesia lisan tidak resmi masyarakat Kotamadya Malang - Soeparno (Universitas Indonesia, Fakultas Pascasarjana, 1991)
Construction of sentences of non formal and oral Indonesian language used by the people in Kotamadya Malang, Jawa Timur Province; doctoral thesis.